2014
DOI: 10.14348/molcells.2014.0258
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Yeast on Emerging Roles of the ATAD2 Protein Family in Gene Regulation and Genome Organization

Abstract: ATAD2, a remarkably conserved, yet poorly characterized factor is found upregulated and associated with poor prognosis in a variety of independent cancers in human. Studies conducted on the yeast Saccharomyces cerevisiae ATAD2 homologue, Yta7, are now indicating that the members of this family may primarily be regulators of chromatin dynamics and that their action on gene expression could only be one facet of their general activity. In this review, we present an overview of the literature on Yta7 and discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…The role of ATAD2 as a regulator of chromatin dynamics is well known in yeast (Cattaneo et al, 2014). A recent study showed that ATAD2 is highly expressed in replicating PC cells and ATAD2 expression correlates with expression of cell cycle and DNA replication genes that have overlapping function in meiosis and tumor progression (Koo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ATAD2 as a regulator of chromatin dynamics is well known in yeast (Cattaneo et al, 2014). A recent study showed that ATAD2 is highly expressed in replicating PC cells and ATAD2 expression correlates with expression of cell cycle and DNA replication genes that have overlapping function in meiosis and tumor progression (Koo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ATAD2 has been shown to be a co-activator of both AR and c-MYC in hormone-responsive human breast and prostate tumors (Ciro et al 2009). The role of ATAD2 as a regulator of chromatin dynamics has been extensively studied in yeast (Cattaneo et al 2014): It is implicated in chromatin structure maintenance and is capable of reading acetyl modifications on histone residues. Koo and colleagues showed that ATAD2 is highly expressed in replicating PC cells, and ATAD2 expression correlated with the expression of cell cycle and DNA replication genes that have overlapping functions in meiosis and tumor progression (Koo et al 2016).…”
Section: Bromodomain-containing Proteins and Chromatin Reprogramming mentioning
confidence: 99%
“…It is validated that disrupting the protein-protein interactions between BET protein and Histone acetylated lysine has emerged as a promising target for various cancers 5 . ATAD2, also known as ATAD2A or ANCCA (AAA nuclear coregulator cancer-associated protein), belongs to the bromodomain and extra-terminal family domain (BET) IV family, could recognise acetylated lysine residues at K5 and K12 on histone H4 6 . ATAD2, as a nuclear protein, mainly expresses in embryonic stem and germ cells which plays an essential role in chromatin remodelling 7 .…”
Section: Introductionmentioning
confidence: 99%